A cold stellar stream in Pegasus - Perottoni, Hélio D; Martin, Charles; Newberg, Heidi Jo [UNESP]; Rocha-Pinto, Helio J.; Almeida-Fernandes, Felipe De; Gomes-Júnior, Altair R. (Oxford University Press (OUP), 2019)
We report the serendipitous discovery of a stellar stream in the constellation Pegasus in the south Galactic hemisphere. The stellar stream was detected using the SDSS Data Release 14 by means of a matched filter in the colour-magnitude diagram that is optimized for a stellar population that is 8 Gyr old with [Fe/H] = -0.46 dex, and located at heliocentric distance of 18 kpc. The candidate stream is faint (turn-off point at r0 ∼19.6), sparse and barely visible in SDSS photometry. It is also detected in the (shallower) Pan-STARRs data. The residual stellar density in the (u - g)0, (g - r)0 colour-colour diagram gives the same estimate for the age and [Fe/H] of this stellar population. The stream is located at a Galactic coordinates (l, b) = (79.4°, -24.6°) and extends over 9° (2.5 kpc), with a width of 112 pc. The narrow width suggests a globular cluster progenitor.
Keywords: Galaxy: halo; Galaxy: stellar content; Galaxy: structure